The Idea of Trademark Rights Valuation as Collaterals: A Financing Solution for Creative Economy Actors - Sri Handayani; Joni Emirzon; Annalisa Yahanan (Badan Strategi Kebijakan Hukum, 2025)
The renewal of intellectual property-based financing schemes represents a groundbreaking solution to help creative economy actors secure loans using their creative assets. This breakthrough has the potential to foster creativity and improve the welfare of these actors. However, the implementation of trademark rights, especially as collateral, is still hampered by the valuation of the trademark rights themselves, what are the challenges of binding trademark rights as collateral and the idea of trademark rights valuation as a financing solution for creative economy actors. The research method used is normative juridical supported by empirical data with a statutory approach, analytical approach, conceptual approach and comparative approach as well as primary, secondary and tertiary legal materials which are analyzed descriptively qualitatively.The research results show, challenges such as difficulties in determining the value of trademark rights, high fluctuations in their value, rampant piracy, and general business risks have led to intellectual property- based businesses being viewed as high-risk ventures. The difficulty in valuing trademark rights, along with their volatility, results in low acceptance of intellectual property-based collateral by financial institutions. Despite this, intellectual property development, which translates creative ideas into viable businesses, requires facilities and support, including financing for the transformation of valuable creative economy concepts. Progress can be made by strengthening technical arrangements, standardizing mechanisms for intellectual property-based financing, establishing valuation procedures for securing trademark rights as collateral, creating appraiser institutions, developing secondary markets, and providing incentives and assistance. These steps will accelerate the implementation of trademark- based financing, ultimately enabling creative economy actors to access capital with legal certainty.